Teachers’ Speaking Strategies in Grade VIII: A Case Study in an Islamic Junior Secondary School in Lampung - Neng Sufia Akmalia; Agus Hidayat; Istiqomah Nur Rahmawati (Universitas Lambung Mangkurat, 2026)
This study explores English teachers’ strategies for developing eighth-grade students’ speaking skills and the challenges encountered during classroom implementation. Using a qualitative descriptive case study design, the research was conducted at an Islamic junior secondary school in Lampung Province, Indonesia, MTs Alpha. Two grade VIII English teachers participated as the primary informants. Data were collected through six classroom observations, two semi-structured interviews, and document analysis. The data were analyzed thematically through systematic coding and categorization, informed by the stages of data condensation, data display, and conclusion drawing/verification. The findings show that the teachers employed a range of Communicative Language Teaching (CLT), oriented strategies to promote students’ oral participation, including role-play, group work, and language games. However, strategy implementation was constrained by low learning motivation, speaking anxiety, limited vocabulary, frequent reliance on the first language, and limited instructional facilities. These findings highlight the importance of pedagogical scaffolding and context-sensitive support when enacting CLT-oriented speaking instruction in EFL classrooms. The study offers practical implications for English teachers and may inform the development of speaking instruction in similar EFL contexts.